URGENSI RETORIKA DALAM AKTIVITAS DAKWAH - Mohd. Rafiq (IAIN Padangsidimpuan, 2015)
AbstractArt and the ability to speak (rhetoric) in front of audiences is needed in various dimensions of life, especially regarding the profession as a da'i. For a preacher (da’i), rhetoric is very vital and urgent to be mastered, because its significance to the way of dakwah islamiyah. Rhetoric intended to convey the truth of the Quran and Hadith, to change the audience to run a of the commanding of Allah to the amar ma’ruf nahi munkar. Practically, rhetoric becomes a necessity for the preacher to be able to carry out the mission of preaching in an orderly, well-planned, structured, conceptualized, and systematic.Many verses of the Qur’an lead preachers to use good rhetoric (fannul khitabah) for doing the activity of dakwah. In surah An-Nahl verse 125, Allah explains that, dakwah activity must be done with hikmah, mau'izhah and Mujadalah. Mujadalah (dialogue in a good way) in this case is understood as a form of rhetoric. Furthermore, the surah Fushilat verse 33 Allah states that the best word (rhetoric) is to call people when carried into the path of Allah (da'wah). It means that calls to the path of Allah is an activity that is best therefore these efforts should also be done in the best way anyway, having 'stance, continuous and without knowing despair coupled with the nature of genuine (sincere) solely because of GodKeyword: Urgency, Rhetoric, Activity, Da'wah AbstrakSeni dan kemampuan berbicara (retorika) di depan khalayak yang dibutuhkan dalam berbagai dimensi kehidupan, terutama mengenai profesi sebagai da'i a. Untuk seorang pengkhotbah (da'i), retorika sangat penting dan segera untuk dikuasai, karena maknanya dengan cara dakwah islamiyah. Retorika dimaksudkan untuk menyampaikan kebenaran Al-Quran dan Hadis, untuk mengubah penonton untuk menjalankan dari perintah Allah dengan amar ma'ruf nahi munkar. Bisa dibilang, retorika menjadi suatu keharusan bagi pendeta untuk dapat melaksanakan misi dakwah secara tertib, terencana, terstruktur, dikonsep, dan systematic.Many ayat-ayat Al-Qur'an menyebabkan pengkhotbah untuk menggunakan retorika yang baik (khitbah fannul ) untuk melakukan aktivitas dakwah. Dalam surah An-Nahl ayat 125, Allah menjelaskan bahwa, kegiatan dakwah harus dilakukan dengan hikmah, mauizah dan Mujadilah. Mujadilah (dialog dalam cara yang baik) dalam hal ini dipahami sebagai bentuk retorika. Selain itu, surah Fussilat ayat 33 Allah menyatakan bahwa yang terbaik kata (retorika) adalah untuk memanggil orang-orang ketika dibawa ke jalan Allah (dakwah). Ini berarti bahwa panggilan ke jalan Allah adalah kegiatan yang terbaik karena itu upaya ini juga harus dilakukan dengan cara yang terbaik pula, memiliki 'sikap, terus menerus dan tanpa mengetahui putus asa ditambah dengan sifat asli (tulus) semata-mata karena Allah.Kata Kunci: Urgensi, Rhetorika, Kegiatan, Dakwah